MAKING HAND SANITIZER FROM NATURAL MATERIALS AN EFFORT TO PREVENT THE SPREAD OF COVID-19 IN TEGALWANGI VILLAGE - Retno Widyani; Nuri Kartini; Pahla Widhiani; Fitri Dian Perwitasari (Ann Publisher, 2024)
The purpose of this PKM activity is to train in making natural hand sanitizers to overcome scarcity during the COVID-19 pandemic. Partners in high school students in Tegal Wangi Village, Cirebon Regency. The method of transferring knowledge and technology with the stages of activities: 1) material briefing, 2) manufacturing practices, and 3) evaluation. The results of this activity are 1) students can understand well the technique of making hand-sanitizers with natural ingredients, this can be seen from the indicator of increasing ability to reach 80%, 2) the skills to make natural hand-sanitizers from natural ingredients, and 3) the availability of natural hand-sanitizer products in the high school environment Tegal Wangi Village, Cirebon Regency. Hand sanitizer-making training activities need to be carried out regularly by utilizing available natural ingredients.